Sex, drugs, and coercive control: gendered narratives of methamphetamine use, relationships, and violence - Copes, Heith (Criminology, 2022)
While many of the motives people provide for using drugs transcend gender, there are also notable gendered differences. These differences in motive talk aid in stigma management, shape gender performances, and can encourage or constrain behavior. Using data from a photoethnography with 52 people who use methamphetamine in rural Alabama, we find that men and women articulate their motives for drug use in distinctly gendered ways. Most notably, men emphasized the benefits of sex on meth while most of the women did not. Men's stories of meth as a sex drug shaped how they interacted with women often leading them to use violence and coercion to control when, where, and with whom women used meth. Women were less likely to say that increased sexual feelings was their primary motive for using meth. They drew on gendered themes of femininity (e.g., motherhood, home keeper) when explaining their drug use. They also sought ways to resist coercive control that were intertwined with their gendered narratives of drug use. The findings point to the importance of gendered narratives in shaping interactions, and significantly, how narratives can contribute to harm and reinforce gender inequality in drug markets.